1981
DOI: 10.3171/jns.1981.55.6.0909
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between visual evoked potentials and intracranial pressure

Abstract: The relationship between intracranial pressure (ICP) and latency of visual evoked potentials (VEP) was investigated in hydrocephalic patients with severe head trauma. A positive correlation of increase in latency of wave N2 (normal latency 71 +/- 9.2 msec) of the VEP with elevations in ICP was observed. A potential role for VEP in both the assessment of shunt function and the monitoring of patients with severe head injury is suggested by these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…Several studies have reported a positive correlation between ICP and F-VEP N2 wave latency with correlation coefficients ranging from 0.83 to 0.84 [89,90]. Similarly, Gumerlock et al found that a F-VEP N2 latency >80 ms linearly corresponded to an ICP > 20 cmH 2 O [91].…”
Section: Visual Evoked Potentials (Veps)mentioning
confidence: 91%
“…Several studies have reported a positive correlation between ICP and F-VEP N2 wave latency with correlation coefficients ranging from 0.83 to 0.84 [89,90]. Similarly, Gumerlock et al found that a F-VEP N2 latency >80 ms linearly corresponded to an ICP > 20 cmH 2 O [91].…”
Section: Visual Evoked Potentials (Veps)mentioning
confidence: 91%
“…The positive correlation between ICP and F-VEP wave latency observed in studies of patients with hydrocephalus suggested this method as a mean to provide an early detection of shunt dysfunction 13,14,16,17,18,19 . Changes in the F-VEP latencies of patients with ICH secondary to cerebral edema have also been observed, and the use of F-VEP has been suggested to monitor ICP in head trauma victims 14,16,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the F-VEP latencies of patients with ICH secondary to cerebral edema have also been observed, and the use of F-VEP has been suggested to monitor ICP in head trauma victims 14,16,17,18 . However, F-VEP in head trauma is biased by other variables as arterial pO 2 , sagittal sinus venous pO 2 and regional cerebral flow and is not an adequate substitute for direct ICP measures 17,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations